A Supercompressible, Elastic, and Bendable Carbon Aerogel with Ultrasensitive Detection Limits for Compression Strain, Pressure, and Bending Angle. Issue 18 (25th March 2018) - Zhuo, Hao; Hu, Yijie; Tong, Xing; Chen, Zehong; Zhong, Linxin; Lai, Haihong; Liu, Linxiang; Jing, Shuangshuang; Liu, Qingzhong; Liu, Chuanfu; Peng, Xinwen; Sun, Runcang
Abstract: Ultralight and compressible carbon materials have promising applications in strain and pressure detection. However, it is still difficult to prepare carbon materials with supercompressibility, elasticity, stable strain–electrical signal response, and ultrasensitive detection limits, due to the challenge in structural regulation. Herein, a new strategy to prepare a reduced graphene oxide (rGO)‐based lamellar carbon aerogels with unexpected and integrated performances by designing wave‐shape rGO layers and enhancing the interaction among the rGO layers is demonstrated. Addition of cellulose nanocrystalline and low‐molecular‐weight carbon precursors enhances the interaction among rGO layers and thus produces an ultralight, flexible, and superstable structure. The as‐prepared carbon aerogel displays a supercompressibility (undergoing an extreme strain of 99%) and elasticity (100% height retention after 10 000 cycles at a strain of 30%), as well as stable strain–current response (at least 10 000 cycles). Particularly, the carbon aerogel is ultrasensitive for detecting tiny change in strain (0.012%) and pressure (0.25 Pa), which are the lowest detection limits for compressible carbon materials reported in the literature. Moreover, the carbon aerogel exhibits excellent bendable performance and can detect an ultralow bending angle of 0.052°. Additionally, the carbon aerogel also demonstrates its promising application as wearable devices. Abstract : A supercompressible, elastic, and bendable carbon aerogel and its ultrasensitive detection performance are presented. The carbon aerogel with lamellar structure and enhanced interaction of reduced graphene oxide layers displays a supercompressibility (an extreme strain of 99%) and ultrasensitive detection limits for strain (0.012%) and pressure (0.25 Pa). The carbon aerogel also shows excellent bendable performance and can detect ultralow bending angles.